2022
DOI: 10.1088/1755-1315/1118/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of organochlorine residues in surface water and mussel Corbicula sumatrana from Lake Singkarak, West Sumatera

Abstract: Organochlorine is a synthetic pesticide that has been banned in many countries because of its high persistence in the environment and can accumulate in animals. The goal of our study was to determine the level of organochlorine residues in surface water and in the mussel Corbicula sumatrana of Lake Singkarak. Water and mussel samples were collected from 10 sampling sites of Lake Singkarak, Batu Taba, Sumpur, Guguk Malalo, Ombilin, Tikalak, Sumani, Saniang Baka, Muaro Pingai, Paninggahan, and Tanjung Mutuih, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This study found higher organochlorine levels in bilih fish than in the surface water of Lake Singkarak (Ibrahim et al, 2022). In bilih fish, organochlorine levels were also higher than in the sediment.…”
Section: Organochlorine and Pyrethroid Residue Of Bilih Fishsupporting
confidence: 41%
“…This study found higher organochlorine levels in bilih fish than in the surface water of Lake Singkarak (Ibrahim et al, 2022). In bilih fish, organochlorine levels were also higher than in the sediment.…”
Section: Organochlorine and Pyrethroid Residue Of Bilih Fishsupporting
confidence: 41%
“…Pyrethrin is a chemical substance has potential as an insecticide that obtained from flower of Chrysanthemum sp. Although, pyrethroid is insecticide modern group that effective and safety compares to the others insecticides such as arsenic, organochlorine, organophosphate, and carbamate but permethrin is still leaving residue in fish and molluscs at Singkarak lake [2]. This condition may be due to permethrin utility out of control around Singkarak lake area.…”
Section: Introductionmentioning
confidence: 99%